Hard X-Ray, Gamma-Ray, and Neutron Detector Physics 1999
DOI: 10.1117/12.366576
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between bulk material defects and spectroscopic response in cadmium zinc telluride detectors

Abstract: One of the critical challenges for large area cadmium zinc teUuride (CdZnTe) detector arrays is obtaining material capable of uniform imaging and spectroscopic response. Two complementary nondestructive techniques for characterizing bulk CdZnTe have been developed to identify material with a uniform response. The first technique, infrared transmission imaging, allows for rapid visualization of bulk defects. The second technique, x-ray spectral mapping, provides a map of the material spectroscopic response when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…5,16 Several studies on CZT detector performance that measured the detector response to narrow collimated g-ray sources noted poor performance at regions of CZT (and CdTe) that are rich in SP, as well as a dependence of the trapping effects with the size of the individual SP heterogeneities as determined by IR microscopy. 3,5,16,17 Despite disagreement emerging from crystal growth groups, a suggested terminology for distinguishing between precipitates and inclusions was given based on processes that occur during crystal growth and cooling. 18,19 The first of these Te-rich phases are the Te inclusions, which may form in melts with excess Te due to thermosolutal instabilities at the solid-liquid interface (without control over melt composition during synthesis).…”
Section: Introductionmentioning
confidence: 99%
“…5,16 Several studies on CZT detector performance that measured the detector response to narrow collimated g-ray sources noted poor performance at regions of CZT (and CdTe) that are rich in SP, as well as a dependence of the trapping effects with the size of the individual SP heterogeneities as determined by IR microscopy. 3,5,16,17 Despite disagreement emerging from crystal growth groups, a suggested terminology for distinguishing between precipitates and inclusions was given based on processes that occur during crystal growth and cooling. 18,19 The first of these Te-rich phases are the Te inclusions, which may form in melts with excess Te due to thermosolutal instabilities at the solid-liquid interface (without control over melt composition during synthesis).…”
Section: Introductionmentioning
confidence: 99%
“…We were able to achieve these large dimensions for our detector with the aid of IR scanning and X-ray screening techniques that allowed us to examine CZT wafers in order to find large homogeneous pieces without defects. 5,6 The first generation detector system tested at Goddard was based on a University of Arizona ASIC designed for medical imaging. This ASIC utilized an integrating amplifier mechanism which read out every pixel each readout cycle, had a 64×64 array of 380 µm pixels, and was constructed so that the CZT detector could be directly connected to the ASIC using indium bump bonding.…”
Section: Detector Test Resultsmentioning
confidence: 99%
“…Several studies on CZT detector performance using collimated gamma ray sources and various types of detector fabrications have attributed poor performance to regions of CZT and CdTe that are rich in Te secondary phases. 17,18,19 These and other studies concluded that these Te-rich areas limit the collection and mobility of electrons (through trapping) and that this factor strongly limits performance in those materials that are being produced with fairly current methodologies. 17 Some researchers have classified these secondary phases as two types of Te-rich phases that form based on processes that take place during crystal growth and cooling.…”
Section: Discussionmentioning
confidence: 97%